Recovering CH4 from Natural Gas Hydrates with the Injection of CO2-N-2 Gas Mixtures - Zhou, Xuebing; Liang, Deqing; Liang, Shuai; Yi, Lizhi; Lin, Fuhua (Energy & Fuels, 2015)
Conversion of natural gas hydrates into CO2 hydrates is well-known as an innovative and eco-friendly method of both future energy production and greenhouse gas control. To increase the total CH4 production rate by using such a method, experiments were carried out by replacing CH4 with gas mixtures containing CO2 and N-2 from naturally occurring CH4 hydrates at 273.9 K and a pressure ranging from 2.50 to 6.67 MPa. Raman spectroscopic analysis was performed to examine the structure and gas distributions in the hydrate phase. Results showed no structural transition in the hydrate phase. CO2 was found to prefer replacing the CH4 in the large hydrate cages, whereas N-2 was found to prefer replacing the CH4 in the small hydrate cages. The total CH4 production was found to increase with addition of N-2. The experimental pressure showed little effect on the CH4 recovery rate with pure CO2. However, with addition of N-2, the CH4 recovery rate was found to decrease and became dependent on the experimental pressure. The transportation of CO2 molecules in the hydrate phase was suggested to be the rate-limiting step, while N-2 captured in hydrate cages slowed the diffusion rate of CO2 in hydrate phase, leading to a lower CH4 recovery rate.